- FUNGSI ANGGARAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA BEKASI SAAT CORONA VIRUS DEASEASE 2019 BERDASARKAN UNDANG-UNDANG PEMERINTAHAN DAERAH: - - Raihan Rifat Rizqulloh; Eko Primananda (Reformasi Hukum Trisakti, 2023)
The budgetary function carried out by the The Regional People's Representative Council (DPRD), according to Law Number 23 of 2014 concerning Local Governance, is implemented through joint discussions with the Local Government regarding the proposed Regional Revenue and Expenditure Budget submitted by the Mayor. The research problem is how the budgetary function of the DPRD in Bekasi City was conducted before and during the Covid-19 pandemic in accordance with Law No. 23 of 2014 on Local Governance. The research was conducted using a normative legal method, utilizing secondary data, and qualitatively analyzing with a deductive conclusion approach. The research findings, discussions, and conclusions reveal that during the Covid-19 pandemic, the formation of the Regional Budget (APBD) stipulated in Minister of Home Affairs Regulation Number 39 involved the Regional Head adjusting the APBD through changes in the Regional Head Regulation regarding the elaboration of APBD, which was then communicated to the DPRD leadership. Under normal circumstances, the stages of APBD formation involve initial discussions between the Local Government and DPRD, in accordance with the explanations in the Law on Local Governance